Virtual power plant in Singapore's electricity market - Lu, Qiaoying (Nanyang Technological University, 2023)
The implementation of Virtual Power Plants (VPPs) in Singapore’s electricity market has the potential to enhance energy efficiency, sustainability, and grid resilience. However, various challenges must be addressed to realize these benefits. These challenges include predicting renewable power and electricity prices in Singapore’s unpredictable climate, modeling VPPs that are suitable for typical HDB and commercial buildings with widely used air-conditioner systems in Singapore, and establishing the VPP participation model in Singapore’s unique electricity market. To address these challenges, this paper proposes several innovative solutions. Firstly, the paper provides an overview of the Singapore electricity market and virtual power plants, comparing different algorithms to improve reliability in forecasting grid operating parameters. The paper then establishes the typical Singapore VPP model that incorporates energy storage, photovoltaic systems, and electric vehicle systems. The optimization is based on the optimization of significant EV and PV resources in Singapore, under several typical scenarios. Finally, the paper studies various cases of VPPs’ participation in the electricity market based on this model. The paper validates the availability of VPPs and concludes by highlighting their potential to reduce costs, improve energy efficiency, and deliver social and environmental benefits.